ESTIMATING PRIMARY AND SECONDARY PRODUCTION OF HCHO IN EASTERN NORTH-AMERICA BASED ON GAS-PHASE MEASUREMENTS AND PRINCIPAL COMPONENT ANALYSIS - Li, S. M.; Anlauf, K. G.; Wiebe, H. A.; Bottenheim, J. W. (GEOPHYSICAL RESEARCH LETTERS, 1994)
Based on atmospheric measurements of multiple species at Egbert, a rural site in Ontario, Canada, during summer 1988, the emission ratios of HCHO/CO and HCHO/SIGMANO(y) for area sources and secondary production of HCHO have been estimated using a modified principal component analysis technique. The technique yields three principal components that represent a photochemically aged air mass, a diurnal cycle, and fresh area emissions. The area emission component has an emission ratio CO/SIGMANO(y) = 9 +/- 3 and SO2/CO = 0.005 +/- 0.003, in agreement with NAPAP area emission data for the eastern US [Buhr et al., 1992]. The emission ratios of HCHO/CO and HCHO/SIGMANO(y) in this component are 0.0056 +/- 0.0022 and 0.05 +/- 0.007, respectively. If these ratios are typical of eastern North American area emissions, the total primary HCHO emission for this region will be 8 x 10(9) moles HCHO annually based on the NAPAP CO emission inventories. Evidence of secondary HCHO production can be found in the photochemically aged component which has considerably higher HCHO/CO (0.016 +/- 0.004) and HCHO/SIGMANO(y) (0.29 +/- 0.03) ratios than the emission ratios. It is estimated that for every 1 ppb NO(x) converted to NO(y), 0.4 ppb HCHO are produced for the ratio (1-NO(x)/NO(y))<0.6; after which the relative HCHO production rate becomes smaller. Using this relative rate, the maximum total HCHO production over the eastern North America is estimated to be 1.3 x 10(11) moles year-1, or approximately 16 times that from primary emission.